Pengaruh Motivasi, Kompetensi, Lingkungan Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai Negeri Sipil pada Kantor Wilayah Kementerian Agama Provinsi Nusa Tenggara Timur - Epu, Bernadinus Asiena; Niha, Simon Sia; Djuang, Gaudensius (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of motivation, competence, work environment and organizational culture which simultaneously and partially have a positive and significant effect on employee performance at the Regional Office of the Ministry of Religion of East Nusa Tenggara Province. The population in this study were all employees at the Regional Office of the Ministry of Religion of East Nusa Tenggara Province, totaling 121 people using census techniques. Data can be collected using questionnaires and documentation studies. The research results show that employee performance at the Regional Office of the Ministry of Religion of East Nusa Tenggara Province can be improved by increasing employee motivation, employee competency, work environment and a supportive organizational culture.